PHOTO-REDUCTION KINETICS OF Mn021N AQUATIC ENVIRONMENTS CONTAINING HUMICACIDS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2008)
ABSTRACT The kinetics of photo-reduction of manganese(IV) oxide, Mn02 in aqueous medium, in the presence of humic acid has been investigated, including the possibility for the involvement of such radicals in the reduction. Results showed that in aqueous medium, the efficiency of the photo-reduction of Mn02 producing a soluble ionic Mn(lI} was governed strongly by an internal electron transfer within an intermediate of HA-Mn02 anion complex, resulted in the chemical adsorption of humic acid on Mn02 surface. It was observed that under solar radiation and atmosphere containing oxygen, the rate of Mn02 reduction increased considerably, by factors of about 46 and 2 respectively. Moreover, there was evidence that some radicals certainly played a role in the photo-reduction of Mn02, since radical scavenger addition significantly decreased the reduction efficiency of Mn02. In the present of an excess of propanol-2, however, which was expected to remove all OH radicals present, only about 60 %decrease in reduction efficiency were observed, suggesting that radicals other than OH radical are involved in the reduction of Mn02. It was observed further that the presence of iron(lII) in Mn02 up to 1 % (w/w) did not alter the reduction efficiency of Mn02. Keywords: Mn02 kinetics, photo-reduction, aquatic, humic acids